Differential Response of Floating and Submerged Leaves of Longleaf Pondweed to Silver Ions - Shabnam, Nisha; Sharmila, P.; Govindjee,; Kim, Hyunook; Pardha-Saradhi, P. (Frontiers in Plant Science, 2017)
In this study, we have investigated variations in the potential of floating and submerged leaves of longleaf pondweed (Potamogeton nodosus) to withstand silver ion (Ag+)-toxicity. Both floating and submerged leaves changed clear colorless AgNO3 solutions to colloidal brown in the presence of light. Transmission electron microscopy revealed the presence of distinct crystalline Ag-nanoparticles (Ag-NPs) in these brown solutions. Powder X-ray diffraction pattern showed that Ag-NPs were composed of Ag0 and Ag2O. Photosystem (PS) II efficiency of leaves declined upon exposure to Ag+; with a significantly higher decline in the submerged leaves than in the floating leaves. Similarly, Ag+ treatment caused a significant reduction in the carboxylase activity of the ribulose bisphosphate carboxylase/oxygenase in leaves. The reduction in this carboxylase activity was significantly higher in the submerged than in the floating leaves. Ag+ treatment also resulted in a significant decline in the levels of non-enzymatic and enzymatic antioxidants; the decline was significantly lower in the floating than in submerged leaves. X-ray photoelectron spectroscopy revealed the presence of Ag2O in these leaves. Inductively coupled plasma mass spectrometry analysis revealed a three-fold higher Ag content in the submerged than in floating leaves. Our study demonstrates that floating leaves of longleaf pondweed have a superior potential to counter Ag+-toxicity compared with submerged leaves, which could be due to the superior potential of floating leaves to reduce Ag+ to less/non-toxic Ag0/Ag2O-nanoparticles/nanocomplexes. We suggest that modulating the genotype of longleaf pondweed to bear higher proportion of floating leaves would help in cleaning fresh water bodies contaminated with ionic forms of heavy metals.